The Changing Stereotypes in Popular Films STEM Themed: On Breaking the Traditional Rigid Values and the Popularisation of Science - Gürkan, Hasan; Echazarreta-Soler, Maria Carmen (Communication Today, 2023)
This study analyses STEM identities in STEM fields represented in popular films. The authors argue that the recently produced big-budget popular films directly or indirectly affirm STEM characters with their portrayal of STEM fields. This analysis focuses on how popular narratives can be an essential tool to communicate the idea that women can be scientists and how they can inspire young women to enter science. These narratives reflect a significant problem in the interactions between the audience and science. The audience thinks the scientists are heroes and the public expect that scientists will automatically accept scientific solutions to problems. Nevertheless, scientists find a solution in these films, and everything gets better. Thus, recent popular STEM-themed big-budget films provide identification with the audience and STEM characters. These narratives construct an alternative STEM discourse by breaking down gender stereotypes and dominant ideology. These films can be coded as films that produce ideology against the dominant ideology and patriarchy, especially regarding STEM, character and gender representation. There is a positive change in the hierarchical order in the STEM field and the representation of women and Others. And these representations do not have any marginalisation.